ADHD and depression: Comorbidity and Therapeutic Approaches in Children - Karanana, Evangelia V.; Karananas, Efthimios V. (Πανελλήνιο Συνέδριο Επιστημών Εκπαίδευσης, 2020)
The aim of thie study is to explore the case of children and adolescents with ADHD and depression. Firstly, the conceptual definition of ADHD and its characteristics are presented. Then comorbidity between ADHD and depression is discussed. In particular, it is examined when this comorbidity occurs, under what circumstances and its justification. In addition, the types of treatment approaches and how the family and school can contribute are presented. Finally, conclusions are made to strengthen the belief of self-efficacy of children-students in order to cope with depression.